2008
DOI: 10.20396/conex.v6i0.8637827
|View full text |Cite
|
Sign up to set email alerts
|

Sexualidade, qualidade de vida e atividade física no envelhecimento

Abstract: Neste artigo abordamos a questão da sexualidade e a atividade física como fatores que influenciam a qualidade de vida no envelhecimento. Conceituamos qualidade de vida em seus aspectos subjetivos e objetivos, e apresentamos o conceito de qualidade de vida no envelhecimento, de acordo com os principais pesquisadores de qualidade de vida e envelhecimento. De acordo com diversos autores, discutimos os fatores que influenciam a avaliação subjetiva da qualidade de vida individual. Abordamos a influência da atividad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…This data is in accordance with the study that indicated the possibility of a relationship between physical exercise practice and more favorable attitudes towards sexuality at an old age. In general, the more sexually active elderly are the ones who regularly practice physical exercise (25) . The data in Table3 demonstrates that women, housewives, widow/widowers and patients presenting associated comorbidities showed significantly greater knowledge about sexuality of the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…This data is in accordance with the study that indicated the possibility of a relationship between physical exercise practice and more favorable attitudes towards sexuality at an old age. In general, the more sexually active elderly are the ones who regularly practice physical exercise (25) . The data in Table3 demonstrates that women, housewives, widow/widowers and patients presenting associated comorbidities showed significantly greater knowledge about sexuality of the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Quality of life is directly related to meeting the needs, wants and desires of individuals, such as sexuality, which requires subjective assessment. 39 The outpatient treatment can allow a space for debate on the subject in order to provide guidance on sexual activity and thus improve the quality of sexual life of patients after CRM.…”
Section: Factors That Negatively Influence the Daily Life After Crmmentioning
confidence: 99%
“…Os hábitos de vida são avaliados quanto a influência na sexualidade de idosos em estudos nacionais 6 e internacionais 7,8 . Os resultados da literatura apontam relação entre estilo de vida e continuidade da vivência sexual, sendo que hábitos de vida menos saudáveis estão relacionados à maiores chances de disfunções sexuais em idosos 6 .…”
Section: Introductionunclassified